Insights into the biocompatibility and biological potential of a chitosan nanoencapsulated textile dye - Costa, Eduardo M. (2022)
Traditionally synthetic textile dyes are hazardous and toxic compounds devoid of any biological activity. As nanoencapsulation of yellow everzol textile dye with chitosan has been shown to produce biocompatible nanoparticles which were still capable of dyeing textiles, this work aims to further characterize the biocompatibility of yellow everzol nanoparticles (NPs) and to ascertain if the produced nanoencapsulated dyes possess any biological activity against various skin pathogens in vitro assays and in a cell infection model. The results showed that the NPs had no deleterious effects on the HaCat cells’ metabolism and cell wall, contrary to the high toxicity of the dye. The biological activity evaluation showed that NPs had a significant antimicrobial activity, with low MICs (0.5–2 mg/mL) and MBCs (1–3 mg/mL) being registered. Additionally, NPs inhibited biofilm formation of all tested microorganisms (inhibitions between 30 and 87%) and biofilm quorum sensing. Lastly, the dye NPs were effective in managing MRSA infection of HaCat cells as they significantly reduced intracellular and extracellular bacterial counts.